ANALISIS MANAJEMEN RISIKO PADA RUMAH PRODUKSI KERAJINAN ANYAMAN SINTETIS MENGGUNAKAN METODE HIRARC - Nur Roikhana Z; Ahmad Saifurriza Effasa; Mutiara Renggani; Alda Yogi Nur S (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Bojonegoro Synthetic Woven Bag Production House is a business that produces bags from synthetic (artificial) materials. Production houses are included in business activities that are followed by risks. The purpose of this research is to identify potential hazards in every production process to product marketing to ensure that the product reaches consumers in goodcondition. This research is included in the descriptive research using the HIRARC method. This method goes through the stages of Hazard Identification, Risk Assessment and Risk Control. The results showed 13 potential hazards and risks from 5 parts of the work area. After identification, then carry out a risk assessment that can be classified into low risk, moderate risk, high risk and extreme risk potential. Of the 13 hazard potentials, there are 3 low risk potentials, 3 moderate risk potentials, 3 high risk potential hazards and 3 extreme risk potential hazards. The potential risks that arise are the reason for the need to implement risk management in synthetic woven bag production houses so that all potential hazards can be minimized if they occur.